Iklim Religius Madrasah dan Pembentukan Karakter Siswa MI - Darmawan, Didit; Mahbubah, Siti Mafridatul (Peneliti.net, 2026)
This study aims to analyze the concept of madrasah religious climate as part of the school environment and its role in shaping the character of Madrasah Ibtidaiyah students. Employing a qualitative literature review method with content analysis, this research synthesizes academic literature to develop a conceptual understanding of how religious climate influences character formation in elementary-aged children. The findings reveal that madrasah religious climate encompasses physical dimensions, ritual practices, social interactions based on Islamic values, teacher role modeling, policies supporting religious values, shared values, and external support from parents and community. Character formation through religious climate occurs through habituation mechanisms that shape positive behavioral routines, role modeling that provides concrete examples, reinforcement that maintains good behavior, internalization that transforms habits into beliefs, and identification that makes values part of students' self-identity. These mechanisms work simultaneously in shaping various character values including honesty, discipline, responsibility, social care, cooperation, love of knowledge, and respect for differences. The effectiveness of character formation depends on the consistency, authenticity, and sustainability of the religious climate, with teachers as frontline agents and principals as primary responsible parties. The study implies that character education cannot rely solely on religious subjects but requires the creation of a holistic and consistent religious climate across all dimensions of madrasah life.